Improving coverage of antenatal iron and folic acid supplementation and malaria prophylaxis through targeted information and home deliveries in Côte d’Ivoire: a cluster randomised controlled trial - Günther Fink; Nicole Probst-Hensch; Jürg Utzinger; Siaka Koné; Daouda Dao (BMJ Global Health)
Introduction Coverage of antenatal iron and folic acid (IFA) supplementation and malaria chemoprophylaxis remains low in many low-income and middle-income settings. We assessed the effectiveness of personal information (INFO) sessions and personal information session plus home deliveries (INFO+DELIV) to increase coverage of IFA supplementation and intermittent preventive treatment in pregnancy (IPTp), and their effectiveness on postpartum anaemia and malaria infection.Methods We included 118 clusters randomised to a control (39), INFO (39) and INFO+DELIV (40) arm, in a trial conducted between 2020 and 2021 with pregnant women (age ≥15 years) in their first or second trimester of pregnancy in Taabo, Côte d’Ivoire. We used generalised linear regression models to assess intervention impact in postpartum anaemia and malaria parasitaemia, and displayed resulting estimates as prevalence ratios.Results Overall, 767 pregnant women were enrolled and 716 (93.3%) were followed up after delivery. Neither intervention had an impact on postpartum anaemia, with estimated adjusted prevalence ratios (aPRs) of 0.97 (95% CI 0.79 to 1.19, p=0.770) for INFO and 0.87 (95% CI 0.70 to 1.09, p=0.235) for INFO+DELIV. While INFO had no effect on malaria parasitaemia (aPR=0.95, 95% CI 0.39 to 2.31, p=0.915), INFO+DELIV reduced malaria parasitaemia by 83% (aPR=0.17, 95% CI 0.04 to 0.75, p=0.019). No improvements in antenatal care (ANC) coverage (aPR=1.05, 95% CI 0.81 to 1.36, p=0.692), IFA (aPR=2.00, 95% CI 0.89 to 4.46, p=0.093) and IPTp (aPR=1.03, 95% CI 0.87 to 1.21, p=0.728) compliance were found for INFO. INFO+DELIV increased ANC attendance (aPR=1.35, 95% CI 1.02 to 1.78, p=0.037) and compliance with IPTp (aPR=1.60, 95% CI 1.41 to 1.80, p<0.001) and IFA recommendations (aPR=7.06, 95% CI 3.68 to 13.51, p<0.001).Conclusions INFO+DELIV can substantially increase compliance with IFA supplementation and improve malaria prevention. However, the increases in IFA supplementation are likely insufficient to address the prevalence of often severe anaemia in this population.Trial registration number NCT04250428.